Manejo de alturas da pastagem de aveia preta mais azevém e uso de suplementação para cabras pré e pós parto - Moro, Valério (2010)
The trial was carried out at IAPAR (Instituto Agronômico do Paraná) in Pato Branco - PR, from April to October 2009 to evaluate two canopy height (12 and 21 cm) either associated or not with energetic supplementation. It was compared two grazing intensities associated or not with energetic supplementation (0.0 e 1.5% of body weight - BW) in 2x2 split-plot design in Completely randomized blocks and three replicates. There were evaluated 36 boer breed goats (55 kg of initial weight) during either pre and pos lambing on black oat (Avena strigosa Schreb) plus annual ryegrass (Lolium multiflorum Lam) pasture. The pastures were continuously stocked using the put and take technique to maintain the height target to each grazing intensity. It was evaluated nutrients and chemical compound dynamic into three depths soil (0-5, 5-10, 10-20 cm). pH-CaCl2, Al saturation, sum of cation, cation saturation, likewise some macro and micronutrients (K, Mg, P, Fe, Mn, Cu, and Zn) were influenced just by sample depth. It can be concluded that 12 cm canopy height plus supplementation, the increase of exchangeable Al can be avoided at deep. As well as, Ca concentration in the soil was increased, which minimize chemical degradation of the soil in grazing lands. Forage accumulation rate was 60 kg DM.ha־¹.day־¹ and 10,283 kg DM.ha־¹ of total forage production was obtained whithin 180 days. Herbage allowance was influenced by period * height, period * supplementation, and supplementation * height interactions. Average herbage allowance was 8.32 and 4.30 kg MS.100-1 kg of BW for 21 and 12 cm of canopy height, respectively. Supplementation affected stocking rate which values were 3,433 and 1,789 kg BW.ha-1day-1 in presence and absence of supplementation, respectively. Average daily weight gain and gain per area were negative. Goat body condition score was affected by treatments, lesser body weight loss was verified in the 21 cm canopy height plus supplementation. Birth weight of kids had no effect neither treatments nor sex. Kids accompanied for their mothers without supplementation grazed 57.76% of grazing time of the goats, and performed better since 25 days old. Goat grazing time was higher in no supplementation treatments, whereas idling time was higher for goats supplemented.